Faculty’s and Students’ Perceptions of Online Learning During COVID-19 - Almahasees, Zakaryia; Mohsen, Khaled; Amin, Mohammad Omar (Frontiers in Education, 2021)
The spread of Covid-19 has led to the closure of educational institutions worldwide, forcing academic institutions to find online platforms. This sit-uation accelerated the development of the online learning environments within those institutions. The Covid-19 pandemic has unfolded the extent of the academic institutions' readiness to deal with such a crisis. In this vein, the study aimed to identify the perception of translation instructors in teaching translation courses online during Covid-19, utilizing a questionnaire to ex-plore the strategies and challenges of teaching and assessing students' per-formance. The analysis revealed instructors' reliance on Zoom and Microsoft Teams in offering virtual classes and WhatsApp in communication with stu-dents outside the class. The findings revealed the relative effectiveness of online education, but its efficacy is less than face to face learning according to the respondents' views. It was also found that students faced difficulties in online learning, which lie in adapting to the online environment, lack of in-teraction and motivation, and the deficiency of data connections. Even though online education could work as an aid during Covid-19, it could not replace face to face instruction. Based on the findings, the study recom-mended blended learning. Combining online education with face-to-face in-struction, i.e., face-to-face plus Synchronous and Asynchronous, would re-sult in a rigorous online learning environment.